Analisis Saluran Distribusi Daging Sapi di Dki Jakarta (Beef Distribution Analysis at DKI Jakarta) - Muh Faturokhman; Ma'mun Sarma; Mukhamad Najib (IPB University, 2015)
Beef price in Jakarta has increasing trends caused by the long chain distribution. The big gap of beef price between producer and consumer showed the distribution chains are less efficient. The objectives of this research to study of distribution channels, marketing margin, the efficiency of marketing and price transmission elasticity of beef in Jakarta. The analytical methods used include margin distribution approach and Cobb Douglas function. Based on the observations, beef and beef cattle distribution channel in traditional markets are: small farmer / beef cattle importir, feedlot industry, regional wholesaler, butcher, slaughter house, grocer, and small retailer. Meanwhile on the modern market are: beef cattle importir/breeding farm and local cattle feedlotter, feedlot industry, slaughter company + beef supplier and modern market stores. Pattern one of live cattle distribution channel has higher marketing margins from small farmer to regional wholesaler and to the butcher with value of 69.73%. The highest marketing margin value of meat distribution is in pattern two from the slaughter company and beef supplier to modern market, then to consumer with value of 39%. Marketing efficiency value to the traditional market beef was 3.47%, meanwhile to the modern market stores was 16.11%. The price transmission elasticity in the six regions of the beef cattle supplier on the meat price at the retail level in Jakarta were 0.788 (Jawa Tengah), 0.923 (Jawa Timur), 0.943 (Jogjakarta), 0.751 (Lampung), 0.762 (NTB), and 0.767 (NTT).Keyword: beef cattles, beef distribution, marketing margin, markerting efficiency, price transmition elasticity